Web-Based Monitoring System for Automatic Coffee Drying in a Smart Dryer Dome - Nofriyanti, Duwi; Handayani, Ade Silvia; Suroso, Suroso; Novianti, Leni; Rakhman, M Arief; Asriyadi, Asriyadi (International Journal of Advances in Data and Information Systems, 2025)
This study developed a web-based monitoring system integrated into a smart dryer dome for automatic coffee drying. The system utilized the RN-GZWS-RS485 sensor to measure critical drying parameters: temperature, humidity, and light intensity. Data acquisition relied on an ESP32 microcontroller, transmitting real-time measurements to a server using the MQTT protocol, while sensor-actuator interactions operated through the Modbus protocol. Actuator performance adhered to predefined threshold values, maintaining drying temperature within 45–50?°C and relative humidity between 20–40%. Real-time monitoring and system status visualization were implemented via a Laravel-based web interface. Experimental tests demonstrated that 71.76% of temperature readings, 64.71% of humidity readings, and 68.24% of light intensity readings consistently fell within optimal ranges. Low standard deviation values confirmed the system’s effectiveness in maintaining stable drying conditions. Additionally, the integration of solar power facilitated system deployment in remote locations without conventional electricity infrastructure. These findings highlight the system's potential to improve the reliability, accuracy, and efficiency of automatic coffee drying processes.